Effectiveness of Group Guidance with the Application of Positive Reinforcement Techniques to Improve Learning Independence at PPA Ibnu Katsir 2 Jember - Mukarromah, Lailatul; Ulwiyah, Imaratul (IAIN Kudus, 2025)
Effectiveness of Group Guidance with the Application of Positive Reinforcement Techniques to Improve Learning Independence at PPA Ibnu Katsir 2 Jember. The purpose of this study was to assess the effectiveness of group guidance using the positive reinforcement method to foster learning independence at the Ibn Katsir 2 Islamic Boarding School in Jember. Learning independence is an important factor in determining learning success. The problem of learning independence, if ignored, will negatively impact achievement. Positive reinforcement techniques are techniques to increase desired behavior by providing pleasant consequences after the behavior is carried out. The purpose of positive reinforcement is to strengthen the behavior so that the behavior is likely to be repeated in the future. This study was a quantitative study with a pre-experimental design type of one group pretest-posttest. The sample for this study was taken using a purposive sampling technique with a total of 48 respondents. After testing, 6 subjects were obtained. Data analysis used the paired t-test Wilcoxon test. The results concluded that there were significant changes in students' learning independence before and after being given treatment. In conclusion, the positive reinforcement technique is effective in increasing learning independence at the Ibn Katsir 2 Islamic Boarding School in Jember. Therefore, this technique can be used further, both in terms of methodology and implementation because this technique is relevant to the culture and values of the Islamic boarding school.Keywords:Group Guidance; Positive Reinforcement; Independent Learning